Study of Absorption Spectra, Fluorescence and Energy Levels of Fluorescein Dye (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The absorption and fluorine spectra of dissolved fluorescein solution in ethanol and different concentrations were studied. The optical properties(absorbance, permeability, linear absorption, and refractive index, as well as time and fluoridation)were calculated. The results showed that a decrease in concentration leads to a decrease in absorption values and an increase in permeability values. This results in a decrease in the values of the absorption coefficient and refractive index. This is in accordance with Lambert's law. Also, the values of the fluorine are lower. The top of the emission spectrum is transferred to the longer wavelengths. The temporal age of fluoride decreases and the quantitative output increases, thus using this dye as an effective laser medium in liquid state lasers. The infrared spectroscopy of the dye was also studied using the (Gaussian 9) program.